Class Standing Differences in Bystander Intervention Intentions to Prevent Sexual Assault: A Reasoned Action Approach - Sarah E. Rush-Griffin; Christine L. Hackman; Paul Branscum; Neha Gautam (New Prairie Press, 2023)
The purpose of this study was to examine differences in determinants of bystander intervention (BI) participation based on undergraduate students' year in school using the Reasoned Action Approach (RAA). Students (n = 291) were recruited from general education courses at two universities in the United States and completed an online survey evaluating intentions, attitudes, perceived norms, and perceived behavioral control (PBC) associated with engaging in BI. Next, attitudes, perceived norms, and PBC were used to predict intentions using separate linear regression models - one model with upper-level students and another model with first-year students. Both models significantly predicted intentions, with the upper-level student model (adjusted R2 = 0.609) accounting for more variance compared to the first-year student model (adjusted R2 = 0.469). When compared to upper-level students, freshman also had significantly greater knowledge, intentions, and perceived norms, PBC and autonomy to engage in BI (p < .05). These findings provide an in-depth understanding regarding the role of class standing in BI behavior. Results indicate students have different reasons for engaging/not engaging in BI based on year in school and support the need for targeted BI reinforcement sessions throughout the college years.